2010
DOI: 10.1177/1938640010378530
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Plantar Fascia Ruptures Following Corticosteroid Injection

Abstract: Plantar fasciitis is commonly treated with corticosteroid injections to decrease pain and inflammation. Therapeutic benefits often vary in terms of efficacy and duration. Rupture of the plantar fascia has been reported as a possible complication following corticosteroid injection. A retrospective chart review of 120 patients who received corticosteroid injection for plantar fasciitis was performed at the authors' institution to determine the incidence of plantar fascia rupture. The plantar fascia rupture was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 9 publications
(8 reference statements)
0
44
0
7
Order By: Relevance
“…The low rates of complications can be attributed to the correct technique and post procedure compliance by the patients. Kim et al [16] performed retrospective study of 120 random patients diagnosed with plantar fasciitis who were treated with local corticosteroid injection and reported the incidence of plantar fascia rupture to be 2.4%, following which it was concluded that corticosteroid injection therapy is a safe and effective form of treatment for plantar fasciitis with minima l complications.…”
Section: Discussionmentioning
confidence: 99%
“…The low rates of complications can be attributed to the correct technique and post procedure compliance by the patients. Kim et al [16] performed retrospective study of 120 random patients diagnosed with plantar fasciitis who were treated with local corticosteroid injection and reported the incidence of plantar fascia rupture to be 2.4%, following which it was concluded that corticosteroid injection therapy is a safe and effective form of treatment for plantar fasciitis with minima l complications.…”
Section: Discussionmentioning
confidence: 99%
“…Kim ve ark., kortikosterid enjeksiyonu ile tedavi edilmiş 120 plantar fasiitis hastasını geriye dönük olarak değerlendirdikleri çalışmalarında, sadece üç olguda rüptür rapor etmişlerdir. [6] Etiyolojide suçlanan diğer nedenler ise, Aşil tendon kontraktürü ve gergin gastrokinemius-soleus kompleksidir. [8] PF rüptürleri nadir görülen yaralanmalar olmakla beraber, sporcularda, popülasyonun geri kalan kısmına göre daha sık izlenir.…”
Section: Sporcularda Plantar Fasya Rüptürleriunclassified
“…Hastalar sıklıkla, atletik aktivite sırasında ani gelişen bir 'pop' sesi ve yırtılma hissi tarif ederler. [6,7] PF rüptürlerinde genellikle, plantarda mediyalde aniden olan keskin ağrı, ayakta, yürürken, koşarken ve parmak ucuna kalkıldığında artan ağrı, lokal hassasiyet, ekimoz ve genel travma bulguları gözlenir. [16] Ayak parmaklarının pasif dorsifleksiyonu ile artan ağrı izlenebilir.…”
Section: Sporcularda Plantar Fasya Rüptürleriunclassified
See 1 more Smart Citation
“…21 Kim, et al, reported on a 2.4% incidence of plantar fascial rupture after receiving an average of 2.67 injections. 22 The injections consisted of .5ccs of dexamethasone plus .5ccs of Triamcinolone, and .5ccs of Xylocaine mixed with .5ccs of Marcaine. Thus far, there have been no reported cases of severe complications from Botox ® injections and platelet plasma injections.…”
Section: Volume 4 No 8 August 2011 the Foot And Ankle Online Journalmentioning
confidence: 99%